Population development and breeding success of Dark-bellied Brent Geese Branta b. bernicla from 1991–2011 - Ebbinge, Bart S.; Blew, Jan; Clausen, Preben; Günther, Klaus; Hall, Colette; Holt, Chas; Koffijberg, Kees; Le Dréan-Quénec’hdu, Sophie; Mahéo, Roger; Pihl, Stefan (Wildfowl, 2013)
The Dark-bellied Brent Goose Branta bernicla bernicla is the largest of the six BrentÂ Goose populations, which collectively number around 600,000 birds globally. After aÂ major decline to 16,500 geese in 1958, numbers recovered during the 1970s andÂ 1980s to a peak of c. 330,000 individuals between 1992 and 1994. From 1994Â onwards the population declined again to 200,000â€“250,000. This decline has beenÂ attributed to poor breeding, associated with faltering cycles of Siberian BrownÂ Lemming Lemmus sibiricus (predominantly) and Palearctic Collared LemmingÂ Dicrostonyx torquatus abundance on the breeding grounds on the Taimyr Peninsula,Â where lemmings are a main food resource for potential predators of goslings. DarkbelliedÂ Brent Geese only breed well in peak lemming years (Summers & UnderhillÂ 1991), and this usually occurs every three years, but the frequent failure since 1994 ofÂ lemming numbers to peak (except in 2005) has resulted in the absence of very goodÂ breeding years for the geese (Nolet et al. 2013). The mid-winter distribution hasÂ shown a marked shift towards France over the last decade. France currently supportsÂ 50% of the population in January, Great Britain 35â€“40%, the Netherlands 15â€“20%, and Germany and Denmark 2%. In spring, almost the entire population gathers in the Wadden Sea, leaving only 4% of the population in Great Britain, and virtually none in France, with the Dutch part of the Wadden Sea supporting 40â€“45%, the German section 45â€“50% and Denmark 6%.